The military institution in the State of magdalena 1857-1885 - Camargo Rodríguez, Ángela Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2011)
The formation process of the modern State includes the monopoly of the Armed Forces as one of the main elements that consolidate it. In the case of Colombia, the control of the Armed Forces has faced great dificulties originated from different political positions that left a mark in national history. During the experience of the Granadina Confederacy and that of the United States of Colombia, from 1857 to 1885, the permanent army was reduced to militias. This paper shows the organization and composition of the armed forces in the Sovereign State of Magdalena during the federal period, aimed to reconstruct the conformation, the establishment and the operation of the military institution in the circumstances of the federation, paying special attention to the way in which both said militias and the army constituted a political force in that region.